Syntax mentioned seven times in the CEFR - and how many times at school, in foreign language classrooms? - Mertelj, Darja (Linguistica (Ljubljana), 2014)
In the teaching of foreign languages, complex-clause syntax does not seem to have had an established role over the last 20 years, especially within the communicative approach and, of course, the CEFR. It was previously part of methods which stressed formal approaches to foreign languages and their being taught, but not of natural, acquisition-based methods. With the communicative approach, two important premises were introduced: authentic texts and grammar as a tool when necessary. This is one probable reason why explicit, complex-clause syntax is hardly mentioned in the CEFR, even though it is implicitly present in descriptors, even though it is particularly recognisable in those for writing skills, and even though we know that it can be used for all four skills, as well as to guide learners towards some self-directed learning about language features. To date, in the era of the communicative approach, not much is known about the role of complex-clause syntax in foreign/second language classrooms, in particular from the learners' viewpoint. In order to bridge this research gap, the paper analyses a questionnaire among learners in secondary schools that looked at their perspectives regarding the (possible) role of syntax. The examined aspects consider its role for the four skills, and the benefits of knowing syntax; implicitly, the paper touches on some affective factors and related methodological approaches, along with problems concerning the teaching of syntax. The findings are based on quantitative data; an evaluation of the need for complex-clause syntax is included, and some pedagogical implications are presented.
Keywords: didactique des langues; didaktika jezika; enseignement des langues; jezikovni pouk; langues romanes; romanski jeziki; sintaksa; skladnja; stališče slovenskih dijakov; syntax; syntaxe; tuji jeziki; večstavčna poved